DEVELOPING COMMUNICATION SKILLS THROUGH SPEECH GAMES IN KINDERGARTENS (Scientific journal of the Fergana State University, 2025)
This article examines the issue of developing communication skills through speech games in kindergarten. The importance of speech games, their types and their role in the development of children's speech are analyzed. The results of the study show that games serve to increase the child's vocabulary, form thinking skills and develop communicative competence.